Evolution of green chemistry and its multidimensional impacts: A review - de Marco, Bianca Aparecida [UNESP]; Rechelo, Bárbara Saú [UNESP]; Tótoli, Eliane Gandolpho [UNESP]; Kogawa, Ana Carolina [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Springer Nature, 2018)
The growing process of industrialization was a milestone for world economic evolution. Since the 1940s, social movements have revolutionized green chemistry and provided shifts in industrial positions and sustainable processes with advances in environmental impact and awareness of companies and population. Paul Anastas and John Warner, in the 1990s, postulated the 12 principles of Green Chemistry, which are based on the minimization or non-use of toxic solvents in chemical processes and analyzes, as well as, the non-generation of residues from these processes. One of the most active areas of Research and Development in Green Chemistry is the development of analytical methodologies, giving rise to the so-called Green Analytical Chemistry. The impacts of green chemistry on pharmaceutical analyzes, environmental, population, analyst and company are described in this review and they are multidimensional. Every choice and analytical attitude has consequences both in the final product and in everything that surrounds it. The future of green chemistry as well as our future and the environment is also contemplated in this work.
Keywords: Future; Green analytical chemistry; Green chemistry; Multidimensional impacts